Legal Protection for Bank Customers for Bank Fund Transfer Errors - Gani Irwansyah, Muh; Saleh, Moh. (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This research aims to analyze the legal protection provided to bank customers in cases of erroneous fund transfers by the bank. The research method used is a normative legal research method with a statutory approach and literature study. This research identifies and analyzes legal regulations that regulate legal protection for bank customers in cases of erroneous fund transfers, such as the Banking Law, Bank Indonesia regulations, and related court decisions. The research results show that bank customers have rights that are protected by legal regulations. If there is an error in transferring funds by the bank, the customer has the right to recover the incorrectly transferred funds, compensation for losses incurred, and compensation for loss of business opportunities or reputation that may occur. This research provides recommendations for improving legal protection for bank customers in cases of erroneous fund transfers. Recommendations include improving existing legal regulations, increasing customer awareness of their rights, and increasing supervision of banks by competent authorities.